Morphology dependent catalysis and surface enhanced Raman scattering (SERS) studies using Pd nanostructures in DNA, CTAB and PVA scaffolds. Issue 29 (17th July 2017) - Kundu, Subrata; Yi, Su-In; Ma, Lian; Chen, Yunyun; Dai, Wei; Sinyukov, Alexander M.; Liang, Hong
Abstract : Palladium nanoparticles (Pd NPs) having three different morphologies have been synthesized by UV-photo activation route. The effect of NP morphology has been tested for the catalysis reaction and in surface enhanced Raman scattering (SERS) studies. Abstract : Palladium nanoparticles (Pd NPs) of three different morphologies viz ., nanocubes with cetyltrimethylammonium bromide (CTAB), nanowires with polyvinyl alcohol (PVA) and Pd NPs with deoxyribonucleic acid (DNA) scaffolds were synthesized by UV-irradiation. Catalysis and surface enhanced Raman scattering (SERS) studies were done with the synthesized morphologically distinct Pd nanostructures for the very first time. The catalytic rate was extremely high with Pd nanowires templated with PVA and the order of the catalytic rate was Pd nanowires in PVA > Pd nanocubes in CTAB > DNA-Pd wire-like assemblies. The highest catalytic rate was observed for PVA capped Pd nanowires which is a few hundred fold higher than other metal NP catalysts. Methylene blue (MB) was used as a Raman analyte for the SERS study and the largest EF of 1.9 × 10 5 at a peak position of 1391 cm −1 was observed with Pd nanowires in the DNA scaffold as a SERS substrate. The order of the SERS EF values was DNA-Pd wire-like assemblies > Pd nanocubes in CTAB > Pd nanowires in PVA. Beyond everything, the present synthesis route is easy, faster, candid, highly reproducible and cost-effective. In the near future, the same protocol could be applied to synthesize other materials for various applications.